The representation of the teaching faculty in the university government Is there alternation? - Rissi, Matilde; Guillermo Oloriz, Mario (Revista Mexicana de Ciencias Agrícolas, 2022)
The exercise of the representation of a certain sector in the government bodies has motivated numerous studies regarding the legitimization of the will of the voter by the representative, as well as respect for the will delegated to those representatives. In the particular case of the National Universities of the Argentine Republic, university co-government and unrestricted admission are two of the principles of university autonomy that are defended and sustained with greater force in the pronouncements of all the faculties that make up said co-government. However, this highly democratic system, although it is of a meritocratic nature given that the weight of representation by faculty is not equal because of the premise that the greatest weight in decision-making should fall on those who would be more prepared for it, the way in which the representation of the faculties is exercised and the renewal of those who exercise it could deteriorate or alter the purpose pursued by whoever occupies that place in representation of the interests of a sector of the university community. In this work, the representation of the teaching faculty in the superior council of a sample of six Argentine national universities, between 2011 and 2017, is analyzed, inquiring about how this representation occurs and is maintained between the different electoral processes. It is concluded that there is a tendency towards a greater repetition of those who exercise the representation in the largest universities or in some of the territorial regions with which the National University System is formed. At the same time, a strong male predominance was found both in the representation with the character of incumbent in the superior council and in the repetition rate in the function.